BIBLIOMETRIC ANALYSIS OF SCIENTIFIC RESEARCH ON THE GENUS LEPIDOSAPHES (Scientific journal of the Fergana State University, 2025)
In this study, a bibliometric analysis of scientific research dedicated to the genus Lepidosaphes was conducted. During the research, articles published in the Scopus, Web of Science, and PubMed databases as of March 2025 were analyzed. Based on the results of the bibliometric analysis, the publication dynamics by years, leading journals, active authors, and leading countries in terms of the number of published scientific works in this field were identified. The analysis results indicate that in recent years, the number of scientific studies on the genus Lepidosaphes has significantly increased, highlighting the high relevance of the topic at the international level.